Lattice Paths: Coding and Complexity - (:unkn) unknown (IEEE, 2009)
We shall study several sequences of numbers arising in the array beta(n, k) = 3 . (n+k k) - 2 . (n+k k-1). Some of them relate to an old problem of Berlekamp, which arose in the construction of certain convolutional burst-error detecting codes. The other sequences are of recent interest in combinatorial theory.